ANALISA IMPLEMENTASI UNDANG-UNDANG NOMOR 45 TAHUN 2009 TENTANG PERIKANAN ( Studi Kasus Upaya Pemerintah Dalam Memberantas Illegal Fishing Di Kepulauan Kapoposang Sulawesi Selatan Periode 2018-2020) - Atiqah Shabrina Adani (2021)
Indonesia is an archipelagic country with most of its territory in the form of waters, therefore the Indonesian state is called a maritime country. The extent of Indonesian waters is vulnerable to cases of theft and destruction of aquatic ecosystems. One of the cases in Indonesian waters, namely Illegal fishing, is a crime committed by foreign ships and domestic ships which refers to Law 45 of 2009 concerning fisheries. One of the government's efforts in overcoming the damage to aquatic ecosystems is to create a water conservation area. However, it does not rule out cases of illegal fishing. As in the case that the author studied in the Kapoposang Aquatic Tourism Park conservation area in South Sulawesi in 2018-2020, there were still violations of illegal fishing. The research question posed is how to implement Law No. 45 of 2009 on fisheries in eradicating cases of illegal fishing in the Kapoposang islands, South Sulawesi. To answer this research question, the author uses the public policy theory of William I. Jenkins. This study uses qualitative descriptive methods and policy analysis methods, which can assist the author in defining policy problems by analyzing data and information relevant to the case under study, as well as conducting indepth interviews with informants. This study discusses how the government's efforts in handling illegal fishing cases in the Kapoposang Islands refer to the implementation of Law 45 of 2009 concerning fisheries.